Biological properties of chitosan/Eudragit E 100 and chitosan/poly(4-vinylpyridine) coatings electrophoretically deposited on AgNPs-decorated titanium substrate - Pawłowski, Łukasz; Akhtar, Muhammad Asim; Zieliński, Andrzej; Boccaccini, Aldo R. (Materials Letters, 2023)
The objective of the study was the determination of the response, in contact with human osteoblast-like MG-63 cells, of electrophoretically deposited coatings composed of chitosan (CS), Eudragit E 100 (EE100), or poly(4-vinylpyridine) (P4VP) on a silver nanoparticle (AgNPs)-decorated titanium substrate. Before deposition, the substrate was coated with silver by electro-reduction of silver nitrate. The coatings deposition was carried out in suspensions containing 0.1 % (w/w) of one of the biopolymers, EE100 or P4VP, with 0.1 % (w/w) of CS for 10 V and 1 min. Biopolymer coatings were successfully deposited while maintaining high uniformity. The deposited silver did not cause cytotoxicity. The biological study revealed that when compared to CS/P4VP, CS/EE100 coating performed better and showed a decrease in MG-63 cell viability only after three days of testing.
CRIS-Team Scopus Importer:2023-02-03
Keywords: Biological properties; Chitosan; Electrophoretic deposition; Eudragit; Poly(4-vinylpyridine); Silver nanoparticles